2022
DOI: 10.3389/fonc.2022.832405
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Directed Treatment Options Following Liver Tumor Recurrence: A Review of the Literature

Abstract: Recurrence following curative-intent hepatectomy for colorectal cancer liver metastasis, hepatocellular carcinoma, or cholangiocarcinoma is unfortunately common with a reported incidence as high as 75%. Various treatment modalities can improve survival following disease recurrence. A review of the literature was performed using PubMed. In addition to systemic therapy, liver-directed treatment options for recurrent liver disease include repeat hepatectomy, salvage liver transplantation, radiofrequency or microw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 153 publications
(196 reference statements)
0
13
0
Order By: Relevance
“…SLT is considered an effective and curative treatment approach that can simultaneously resolve liver tumors, potential liver dysfunction and the original underlying diseases. For recurrent HCC, as long as patients meet the criteria, the prognosis is relatively high[ 11 , 82 , 83 ]; the 5-year survival rate is 42%-73%[ 84 ]. A systematic retrospective analysis of the prognosis of SLT and RR in the treatment of recurrent HCC showed that patients in the SLT group generally had larger liver lesions but better relapse-free survival (RFS) than those in the RR group and that the OS of the two groups was similar[ 85 ].…”
Section: Liver-targeted Local Therapy Still Dominatesmentioning
confidence: 99%
See 1 more Smart Citation
“…SLT is considered an effective and curative treatment approach that can simultaneously resolve liver tumors, potential liver dysfunction and the original underlying diseases. For recurrent HCC, as long as patients meet the criteria, the prognosis is relatively high[ 11 , 82 , 83 ]; the 5-year survival rate is 42%-73%[ 84 ]. A systematic retrospective analysis of the prognosis of SLT and RR in the treatment of recurrent HCC showed that patients in the SLT group generally had larger liver lesions but better relapse-free survival (RFS) than those in the RR group and that the OS of the two groups was similar[ 85 ].…”
Section: Liver-targeted Local Therapy Still Dominatesmentioning
confidence: 99%
“…Consequently, the prognosis after treatment varies greatly, but overall, TACE can improve the OS of multifocal tumor patients. A number of studies have shown that the 5-year survival rate after TACE treatment for recurrent HCC is 12-56%[ 70 , 83 , 84 , 87 , 96 ]. A prospective study showed that for patients with early HCC recurrence, the 5-year survival rate after TACE treatment was 27.7%, which is lower than those for RR and RFA.…”
Section: Liver-targeted Local Therapy Still Dominatesmentioning
confidence: 99%
“…To date, the available options for RHCC were similar to naïve-HCC options and include LR, OLT, and LRT for patients with liver-only recurrence, TACE, TARE, and stereotactic ablative radiotherapy for patients with unresectable disease, and systemic therapies or enrollment in clinical trials for patients with extrahepatic disease recurrence[ 13 - 15 ].…”
Section: Lrtmentioning
confidence: 99%
“…To overcome the shortcomings of RFA, MWA has been assessed in the treatment of HCC, as it produces significantly larger areas of necrosis, faster ablation times, higher intratumor temperature, less tumor seeding risk, and less susceptibility to heat-sink effect over RFA[ 15 , 23 ] (Figure 1 ). However, there are few studies about percutaneous MWA performance in RHCC.…”
Section: Lrtmentioning
confidence: 99%
“…The recommended therapies for intermediate-stage HCC, BCLC stage B, are intra-arterial therapies and stereotactic body radiation therapy 9 and the standard of care is transarterial chemoembolisation (TACE), which has been used worldwide since the 1980. 10 In TACE, a chemotherapeutic drug is delivered through a catheter placed in the liver artery, with or without the addition of an embolising agent ( figure 1 ).…”
Section: Introductionmentioning
confidence: 99%